Monopólio postal à luz do direito constitucional e do direito antitruste: um estudo comparado das experiências européia e norte-americana - Gaban, Eduardo Molan (2011)
The paper refers to the elaboration of a hermeneutic line of investigation for the postal monopolies, aiming to demonstrate its incompatibility with the 1988 Federal Constitution, through a multidisciplinary approach grounded in the disciplines of constitutional and antitrust law. Through an optical analysis of the possible effects to society, the question of whether Brazil should maintain its legal monopoly within the postal services was discussed; more specifically, would the 1988 Constitution have approved the infraconsitutional legislation (which constitutes the legal basis for the postal monopoly in Brazil) recognizing their compatibility/harmonization with the constitutional principles of free economic enterprise and free competition, which structure the current economic order. A comparative study was developed on the US and EU experiences, which contributed to better evaluate the arguments and the grounds underlying the Brazilian postal monopoly. Therefore, good propositions emerged to improve the Brazilian model for the postal services. It was concluded that the monopoly model, used by State owned companies, is not the ideal model for the postal services. In Brazil s specific case, it is not compatible with the 1988 Federal Constitution. It would, therefore, not be possible to harmonize the previous legislation, which instituted the legal monopoly (Legal Decree n. 509/1969 and Law n. 6538/1978)